Management of Senile Atopic Dermatitis in Geriatric Outpatient Clinic Dermatovenereology Department Cipto Mangunkusumo Hospital in 2011-2015 (Global Journal of Medical Research, 2018)
Background and objective: Senile atopic dermatitis is atopic dermatitis (AD) which persists until elderly or the onset first occur in elderly. Though it is relatively uncommon, the number of patients are gradually increasing in industrialized countries associated with aging society. The prevalence of senile AD remains unclear, and in Indonesia, there has not been any study regarding senile AD yet. Until now, there is no life-long cure for atopic dermatitis. Management comprises of treatment to protect the skin barrier, anti-inflammatory, and the identification and avoidance of trigger factors. Method: This is a retrospective descriptive study. Secondary data was obtained from CiptoMangunkusumo Hospital medical record. Result: In five year period, there were 54 senile AD patients with female predominance. Most patients were in 60-69 years old group (63%) and 31 of 54 patients were unemployed or already retired (57.4%). The most common type of onset was senile onset, which found in 45 patients (83.3%). Based on severity, most cases (58%) were classified as a moderate senile AD and treated with intermittent use of mid-potency topical corticosteroid, as well as regular application of emollient. Conclusion: On observation, the number of senile AD cases are increasing along with the increasing number of geriatric population and it should not be underestimated. Proper management of senile AD may improve patients’ quality of life.
Keywords: geriatric; profile; senile atopic dermatitis; treatment